Evaluation of heavy metals exposure through air using nails and salivary interleukin-6 among children living close to solid waste landfills in Malaysia - Jamaluddin, Dora Esphylin (2018)
Prolonged exposure to particulate matter (PM10) pollution from municipal solid waste (MSW) landfills may produce some health effects especially in children. This study evaluates heavy metals exposure through air using nails and salivary interleukin-6 as a biomarker among children living close to solid waste landfills in Malaysia. This cross-sectional study was conducted from May to July 2014 among children living close to solid waste landfills in four states of Peninsular Malaysia. The operating municipal solid waste (MSW) landfill sites in this study were selected based on the landfill type through levels classification which is landfill Level 1; a non-sanitary landfill with daily soil covering, landfill Level 2; a non-sanitary landfill with ban and daily soil covering and landfill Level 3; a non-sanitary landfill with leachate collection pond. Three sub-studies include; 1) environmental assessment, 2) biomarker analysis and, 3) health risk assessment was performed to meet the study objectives. In sub-study 1, heavy metals concentration in PM10 collected in the MSW landfill sites, exposed residential areas (within 3-km radius from MSW landfills) and unexposed residential areas (beyond 3-km radius from MSW landfills) from the air samples were determined. Heavy metals concentrations were compared with the international and national air quality standards. The heavy metals in PM10 were analysed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The highest mean concentration among all the heavy metals in the MSW landfills and residential areas was Al with the mean ± SD of 117.25 ± 23.43 μg/m3 particularly in landfill type-level 1. Only three elements were found significantly higher; Al (p<0.001), Cd (p<0.05), and Ni (p<0.05), particularly in landfill type-Level 1, when compared to other landfill types. In the sub-study 2, the presence of these heavy metals in fingernails and IL-6 in saliva as biomarker samples of the exposed and unexposed children were determined and compared. Questionnaire forms were distributed among 342 children aged 7 to 12 years. An adapted Children Health Questionnaire form (CHQ) was applied in the survey. The heavy metals in fingernail samples were analysed using an inductively coupled plasma mass spectrometry (ICP-MS). The IL-6 level was analysed using an enzyme-linked immunosorbent assay (ELISA) method. The heavy metals in fingernails of the exposed children were significantly higher compared to those in the unexposed group. The IL-6 level also was significantly higher (p<0.05) among exposed children with the mean ± SD of 5.52 ± 1.31pg/ml compared to the unexposed children (5.19 ± 1.17pg/ml). In the sub-study 3, the association of PM10 heavy metals in air, heavy metals accumulation in fingernails and IL-6 level with reported health symptoms are determined and children health risks were calculated. Results had showed that runny nose and sneezing were significant difference among the exposed and unexposed group respondents with p<0.05. Children without pets had lesser risk of the respiratory symptoms. High levels of heavy metals in PM10 and in fingernails were associated with higher risks of reported respiratory symptoms. Heavy metals in PM10 and fingernails were associated with potential risk factors of respiratory health. Non-carcinogenic and carcinogenic health risk showed that no risk exists via ingestion, inhalation and dermal route for both groups in the study areas. In conclusion, children living less than 3-km radius from MSW landfills are likely to experience potential health risks due to exposure to the PM10 heavy metals.